2016
DOI: 10.1080/02755947.2016.1165772
|View full text |Cite
|
Sign up to set email alerts
|

Daily Increment Validation and Effects of Streamflow Variability and Water Temperature on Growth of Age‐0 Flathead Chub

Abstract: We studied age‐0 Flathead Chub Platygobio gracilis through two reproductive seasons in Fountain Creek, Colorado, to better understand effects of hatching date, water temperature, and streamflow on daily growth rates. Analysis of laboratory‐reared Flathead Chub of known age confirmed that daily growth increments were deposited in otoliths beginning at hatching and at a rate of one per day thereafter. That information enabled relatively accurate and unbiased estimation of age and daily growth rates of age‐0 fish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 43 publications
2
16
0
Order By: Relevance
“…A fourth candidate for LP/P‐BS reproduction is Tamaulipas shiner. This species inhabits large‐stream habitats of the Rio Grande system, which supported six other cyprinid PBS species (Haworth & Bestgen, ; Platania & Altenbach, ). To our knowledge, Tamaulipas shiner previously has not been considered a LP/P‐BS candidate, but a recent phylogenetic analysis placed it in Alburnops as sister to the LP/P‐BS species, Red River shiner (Hollingsworth et al., ).…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…A fourth candidate for LP/P‐BS reproduction is Tamaulipas shiner. This species inhabits large‐stream habitats of the Rio Grande system, which supported six other cyprinid PBS species (Haworth & Bestgen, ; Platania & Altenbach, ). To our knowledge, Tamaulipas shiner previously has not been considered a LP/P‐BS candidate, but a recent phylogenetic analysis placed it in Alburnops as sister to the LP/P‐BS species, Red River shiner (Hollingsworth et al., ).…”
Section: Resultssupporting
confidence: 66%
“… References: 1 Platania and Altenbach (); 2 Hoagstrom and Turner (); 3 Coleman (); 4 G. Wilde unpublished data; 5 Hoagstrom, Hayer, et al. (); 6 Albers and Wildhaber (); 7 Simon (); 8 Haworth and Bestgen (); 9 K. Bestgen unpublished data; 10 Flittner (); 11 Williams and Bonner (). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Daily age was estimated for age‐0 fish ( n = 34) as the number of daily rings on otoliths, assuming that increments were first deposited at hatching. The initiation of daily growth rings on otoliths at hatching has been reported in several species, including Flathead Chub Platygobio gracilis (Haworth and Bestgen ) and Smallmouth Bass Micropterus dolomieu (Hill and Bestgen ). Likewise, initiation of daily growth rings on otoliths has been observed before and after hatching.…”
Section: Methodsmentioning
confidence: 92%
“…In this analysis, the CPUE for FHC of less than or equal to 6 cm total length was used to represent age-0 individuals. Age and growth analysis of FHC in FCB near site 8 found that individuals less than or equal to 6 cm total length in the fall were likely hatched that year and are of the age-0 year class (Haworth and Bestgen, 2016). These annual estimates of age-0 FHC were compared to patterns of peak flow days (in the sense of Haworth and Bestgen, 2017; see the discussion on peak streamflow).…”
Section: Selected Speciesmentioning
confidence: 99%